Metrological support of pulse oximeters - Tverytnykova, Elena; Drozdova, Tatyana; Demidova, Yu. Ye.; Kuzmenko, Nataliia (Національний технічний університет "Харківський політехнічний інститут", 2022)
The experience of the International Medical Device Regulators Forum in the use of products for oxygen therapy based on the study of guidelines, international and European regulations on medical devices is considered. Emphasis is placed on issues related to the metrological support of pulse oximeters. The global situation with the pandemic increases the relevance of selected topics. Continuous monitoring of blood oxygen saturation is one of the most important elements in the diagnosis and treatment of COVID-19. Despite the fact that the use of pulse oximeters does not require special medical knowledge, calibration and special maintenance, it is still necessary to control their reliability and accuracy of measurement. The study of pulse oximeter MD300M in accordance with the requirements of DSTU 8893:2019 "Metrology. Pulse oximeters. Calibration Method" 2020. Analysis of MD300M pulse oximeter calibration results revealed that this pulse oximeter was calibrated by the saturation and pulse measurement channel, as the maximum deviation of the measured saturation value from the pulse oximeter calibration measure does not exceed the pulse oximeter measurement documentation specified in the operating documentation. The discreteness of the MD300M pulse oximeter and the discreteness of the reference device MPPO-2, which are specified in the passports for the respective devices, have the greatest influence on the measurement uncertainty.

Розглянуто досвід організації International Medical Device Regulators Forum із застосування виробів для кисневої терапії на основі дослідження методичних рекомендацій, міжнародних та європейських нормативних документів щодо виробів медичного призначення. Акцентовано увагу на питання, пов’язані з метрологічним забезпеченням пульсоксиметрів. Світова ситуація з пандемією підсилює актуальність обраної теми. Постійний моніторинг рівня насиченості крові киснем тобто сатурації є одним з важливіших елементів діагностики та лікування COVID–19. Незважаючи на те, що використання пульсоксиметрів не потребує спеціальних медичних знань, калібрування та особливого обслуговування, все-ж таки необхідно контролювати їхню надійність і точність вимірювання. Проведене дослідження пульсоксиметру MD300M згідно вимогам ДСТУ 8893:2019 "Метрологія. Пульсоксиметри. Методика повірки" 2020 р. Аналіз результатів повірки пульсоксиметра MD300M виявив, що даний пульсоксиметр пройшов повірку за каналом вимірювання сатурації та пульсу, оскільки максимальний відхил виміряного значення сатурації від заданого мірою для повірки пульсоксиметрів не перевищує зазначеної в експлуатаційній документації на пульсоксиметри абсолютної похибки вимірювання сатурації. Найбільший вплив на невизначеність вимірювання мають дискретність пульсоксиметра MD300M та дискретність еталонного приладу МППО-2, що зазначені в паспортах на відповідні прилади.
Метрологічне забезпечення пульсоксиметрів
Keywords: metrological support; pulse oximeter; COVID-19; verification; international standards; метрологічне забезпечення; пульсоксиметр; повірка; міжнародні стандарти